Review on Nanomaterials and Their Utilization in the Recovery of Waste Mechanical Energy by Using Piezoelectric Nanogenerators - Mishra, Sakshi (Asian Review of Mechanical Engineering, 2019)
Nano scale materials are defined as a set of substances where at least one dimension is less than approximately 100 nanometers. A nanometer is one millionth of a millimeter- approximately 100,000 times smaller than the diameter of a human hair. Nanomaterials are of interest because at this scale unique optical, magnetic, electrical, and other properties emerge. These emergent properties have the potential for great impacts in electronics, medicine, and other fields. Energy harvesting from the environment is one of the core features of a functional, self-sufficient nanosystem. Self-powered nanosystems combine the nanogenerator with functional nanodevices in order to harvest mechanical energy from the environment into electricity to power nanodevices. It can work independently, without any other external power sources. Piezoelectricity is the electric charge that accumulates in certain solid materials (such as crystals, certain ceramics, and biological matter such as bone, DNA and various proteins) in response to applied mechanical stress.Energy harvesting (or power scavenging) refers to capturing energy from environment, surrounding system or any other source and converting it into a usable form of energy to develop self-power system that doesn’t need external power supply e.g. piezoelectric process. In order to harvest the waste mechanical energy during various processes, piezoelectric properties of different materials such as ZnO can be utilised in order to convert the waste mechanical energy into electrical energy which could further be used.